Development of Contextual Integrated Electronic Temperature and Heat Modules Based on Qur’an Verses at MTsN 3 Tulungagung - Fildaniyah, Masroul; Abbas, Muhammad Luqman Hakim (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
This research contributes to the priorities of "Merdeka Belajar 2021", digitization of schools and learning media, and character education. This study used research and development (R&D) by Borg and Gall, modified by Sugiyono. In this method, there were ten research steps, which are then limited to seven steps. The seven steps are potential problems, data collection, product design, design validation, design revision, product testing, and product revision I. The instruments used came from the validation sheets of material and media experts, as well as electronic module readability questionnaires from MTsN 3 Tulungagung students. Data analysis used linkert scales 1-4. Validation results from media and material experts show valid criteria based on the attractiveness of the appearance and depth of the material, both in terms of contextual aspects and its integration with the Qur’an. Based on the test results, the electronic module is very interesting because it is presented interactively.